Recognition of Indigenous Peoples Values in Indonesia for Policy Addressing Climate Change - Rafiqi, Ilham Dwi (Journal of Law and Legal Reform, 2025)
Climate change has a significant impact on vulnerable communities; one of which is indigenous people. The dependence and closeness of indigenous people to the environment and natural resources have indicated that they must be the first to experience the negative impacts of climate change. This abstract focuses on the need of policy reform and strategies to deal with climate change in Indonesia through recognition of the environmental values amidst indigenous people. The current management of climate change in Indonesia shows that there are gaps and weaknesses in the participation of indigenous people for policy making and moves for climate change mitigation and adaptation. The article begins by explaining the guarantee of legal protection and identified the rights of people who are disturbed by the impacts of climate change, including examining whether existing climate change policies in Indonesia are in favor of indigenous people. Apart from that, the exportation of environmental values depicted by indigenous people in Indonesia is also a basis for proposing recognition about climate change handling policy strategies. To answer legal questions, legal and literature studies were chosen. The proposed recognition of environmental values would aim to protect and maintain the existence of indigenous people amidst the threat of climate change. Research findings would become suggestions to the government, starting with reforming problematic policies to taking further steps in recognition of prescribed environmental values. At the end, this article is strongly expected to contribute significantly to the midst of 'climate legislation' and the on-going formulation to generate strategies policy for handling climate change in Indonesia. For existing conditions, this article serves to be a consideration for the need of legal reform in handling climate change policy related to indigenous people.